Fostering Energy Efficiency Through Street Lighting System Improvement: A Case Study of City-Level in Indonesia - Kurniawan, Irwan Wahyu; Kurniawan, Robi (Purnomo Yusgiantoro Center, 2022)
Street lighting can be considered the main energy consumer and greenhouse gas emitter at Indonesia's city level. In addition, public street lighting systems throughout Indonesia still use inefficient technologies, resulting in a significant portion of a municipality’s operating expenditure. We conduct techno-economy analysis and formulate financing mechanisms to support energy efficiency improvements on street lighting systems. In doing so, a pilot case based on a survey in one of the provincial capitals in Kalimantan is performed. From the survey, it is found that around half of the street lighting systems in the observed city are unmetered, dominated by CFL (Compact Fluorescent Lamp) lamps. Efficiency through street lighting system improvement can be achieved through, among others, replacement with a highly efficient light-emitting diode (LED) lamp, power meters installation and the replacement of high-efficiency armatures. Our analysis shows that energy consumption reduction potential from street light system improvements can reach 69% from existing conditions. In the showcase, it can save 9,466,465 kWh, equal to energy costs of IDR 13,676,202,724 and a 7,667-ton emission reduction. From the analysis, we also delivered a financial scheme for the project that incorporated local government and special mission vehicles under the coordination of the Ministry of Finance. Having great potential, a financing support mechanism can become a reference to another local government with a limited budget constraint. These findings can also provide policymakers with important inputs while improving street lighting systems as a key service provided by local and municipal governments.